2009
DOI: 10.1177/0269215508099862
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of isokinetic exercise versus standard exercise training in patients with chronic low back pain: a randomized controlled study

Abstract: Isokinetic and standard exercise programmes have an equal effect in the treatment of low back pain, with no statistically significant difference found between the two programmes. The standard exercise programme was easily performed and had a low cost, making it the preferred option for exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
(66 reference statements)
1
29
0
4
Order By: Relevance
“…Other possible explanations are that they derive from more central effects [14][15][16][17][18][19][20], perhaps as a correction of a distorted ''body schema'' [4,14] or altered cortical representation of the back [22][23][24][25], from modification of motor control patterns as a consequence of a reweighting of sensory input [21], or simply from a positive therapistpatient interaction/relationship [26]. Several studies have reported a correlation between psychological status and low back pain or pain tolerance [15,58,[75][76][77][78]. The efficacy of treatments that solely focus on psychological targets has, however, been shown to be small [4].…”
Section: Discussionmentioning
confidence: 99%
“…Other possible explanations are that they derive from more central effects [14][15][16][17][18][19][20], perhaps as a correction of a distorted ''body schema'' [4,14] or altered cortical representation of the back [22][23][24][25], from modification of motor control patterns as a consequence of a reweighting of sensory input [21], or simply from a positive therapistpatient interaction/relationship [26]. Several studies have reported a correlation between psychological status and low back pain or pain tolerance [15,58,[75][76][77][78]. The efficacy of treatments that solely focus on psychological targets has, however, been shown to be small [4].…”
Section: Discussionmentioning
confidence: 99%
“…(41) Other studies have shown that different resistance exercise programs can reduce low back pain symptoms. (3, 16, 17, 26, 30) Resistance exercise also results in favorable psychosocial benefits such as reduction of anxiety and fear of falling, both of which can contribute to increased physical function and activity. (19, 22) It is unclear, however, if resistance exercise protocols reduce perceived disability due to LBP and fear avoidance beliefs and pain catastrophizing in the obese, older adult.…”
Section: Introductionmentioning
confidence: 99%
“…Sertpoyraz et al 23 saw increased lumbar extension strength and reduced self-reported pain in patients after participation in an isokinetic RT programme; however, the results were not significantly different when compared with a standard therapeutic exercise programme. Unfortunately, the authors failed to provide a description of the standard exercise programme, thus making a direct comparison of the two training programmes difficult.…”
Section: Resultsmentioning
confidence: 96%